First-in-Human study of JNJ-55920839 in healthy volunteers and patients with systemic lupus erythematosus: a randomised placebo-controlled phase 1 trial. (October 2020) - Jordan, Jarrat; Benson, Jacqueline; Chatham, Walter Winn; Furie, Richard Alan; Stohl, William; Wei, James Cheng-Chung; Marciniak, Stanley; Yao, Zhenling; Srivastava, Bhaskar; Schreiter, Jessica; Cesaroni, Matteo; Orillion, Ashley; et al.
Summary: Background: Activation of the type I interferon (IFN) pathway is associated with systemic lupus erythematosus (SLE). We assessed the safety and tolerability of JNJ-55920839, a human monoclonal antibody that selectively neutralises most human IFNα subtypes and IFNω, in healthy participants and those with SLE. Methods: This was a two-part, first-in-human, phase 1, randomised, double-blind, placebo-controlled, multicentre study of single-ascending intravenous doses of 0·3–15 mg/kg or a single subcutaneous dose of 1 mg/kg JNJ-55920839 administered to healthy participants (part A) and multiple intravenous doses of 10 mg/kg JNJ-55920839 administered to participants with SLE (part B). Healthy men and women (women had to be postmenopausal or surgically sterile) aged 18–55 years; bodyweight of 50–90 kg; and body-mass index (BMI) of 18–30 kg/m 2 were eligible for inclusion in part A. Men and women with SLE were recruited to part B, fertile female participants were required to have a negative pregnancy test result before and during the study and be using two highly effective methods of birth control. The inclusion criteria for participants with SLE in part B matched part A, except for bodyweight (40–100 kg). In both parts, participants were randomly assigned (3:1) to receive JNJ-55920839 or placebo; a computer-generated randomisation schedule was used in part A, and randomisation was stratified by racial and ethnic subpopulation and elevated levels of serological disease activity in part B. The primary outcome was evaluation of safety and tolerability of the study regimen assessed using clinical and laboratory tests compared with placebo. This study is registered with ClinicalTrials.gov, NCT02609789 . Findings: Between Dec 11, 2015, and Sept 20, 2018, 48 healthy participants from a single site and 28 participants with mild-to-moderate SLE from 19 participating centres in seven countries were enrolled in the study. 12 healthy volunteers in part A and eight participants with SLE in part B received placebo. The most common treatment-emergent adverse events in both part A and B were in the system organ class of infections and infestations with a higher percentage of participants administered JNJ-55920839 with infections (ten [28%] of 36 in part A and nine [50%] of 18 in part B) than those exposed to placebo (two [17%] of 12 in part A and one [13%] of eight in part B). Particpants in part B were permitted to continue on defined ongoing standard of care medications. In two participants with SLE, locally disseminated herpes zoster of the skin was reported. No other clinically significant safety or tolerability issues were identified beyond the infections observed in participants treated with JNJ-55920839. Interpretation: JNJ-55920839 was well tolerated and safe. Additional studies are warranted to determine optimal dosing of patients and further explore safety. Funding: Janssen.